2018
DOI: 10.5937/ffr1802193c
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of linseed-sunflower meal co-extrudate: Process prediction

Abstract: For many years, linseed has been attracted a great attention in animal nutrition because of its exceptionally favourable fatty acid composition and high content of essential α-linolenic acid. However, the presence of antinutritive components, cyanogenic glycosides, limits its inclusion in the animal's diet. Several ways of linseed detoxification were observed in literature, emphasizing extrusion as one of the most effective processes. In the presented study, the application of Artificial Neural Network (ANN) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…At a certain extrusion temperature (125–145 °C), the EPA and DHA contents of the extrudates decreased dramatically as the moisture content increased from 65% to 75%. Čolović et al 50 also found that increasing the moisture content could lead to less fatty acid contents during the high-moisture extrusion processing because of the inactivated lipase. However, when the moisture content was at 70%, as the extrusion temperature increased from 125 °C to 145 °C, the EPA and DHA contents increased significantly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At a certain extrusion temperature (125–145 °C), the EPA and DHA contents of the extrudates decreased dramatically as the moisture content increased from 65% to 75%. Čolović et al 50 also found that increasing the moisture content could lead to less fatty acid contents during the high-moisture extrusion processing because of the inactivated lipase. However, when the moisture content was at 70%, as the extrusion temperature increased from 125 °C to 145 °C, the EPA and DHA contents increased significantly.…”
Section: Resultsmentioning
confidence: 99%
“…It might be caused by lipid oxidation and thermal decomposition according to a study. 50 Wang et al 52 also reported that fatty acids were broken down due to the action of high temperature, high pressure and high shear. It is generally believed that fatty acids can form complexes with carbohydrates and proteins in the extrusion process.…”
Section: Fatty Acid Evaluationmentioning
confidence: 99%